2012
DOI: 10.1136/neurintsurg-2012-010544
|View full text |Cite
|
Sign up to set email alerts
|

Safety and cost of stent-assisted coiling of unruptured intracranial aneurysms compared with coiling or clipping

Abstract: SAC is a safe alternative to coiling or clipping of unruptured aneurysms but it is currently more expensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The shorter waiting time has to be considered in the clinical use of the novel LEA PHIL. 18 There were some limitations to our study. First, the number of trials was small.…”
Section: Discussionmentioning
confidence: 93%
“…The shorter waiting time has to be considered in the clinical use of the novel LEA PHIL. 18 There were some limitations to our study. First, the number of trials was small.…”
Section: Discussionmentioning
confidence: 93%
“…The use of stents and stent-like devices for the treatment of acutely ruptured aneurysms is still controversial even though several studies have demonstrated that the complication risk of stent-assisted coiling is comparable to both simple coiling and clipping 12 13. Recently, Roh et al compared their experience with stent-assisted and no-stent-assisted coil embolization in the treatment of ruptured aneurysms and found similar clinical and angiographic outcomes between both techniques 14.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of an intracranial stent is approximately USD 5,200 for the Enterprise (Codman Neurovascular) and USD 5,315 for the Neuroform (Stryker, Kalamazoo, Mich., USA) [21]. In comparison, the list price of the Ascent balloon (Codman Neurovascular) as obtained from their regional sales office is USD 1,607, which is a fraction of the cost of an intracranial stent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these elevated risks, there is a significant additional cost associated with the use of SAC [21]. The cost of an intracranial stent is approximately USD 5,200 for the Enterprise (Codman Neurovascular) and USD 5,315 for the Neuroform (Stryker, Kalamazoo, Mich., USA) [21].…”
Section: Discussionmentioning
confidence: 99%